PENGARUH DERAJAD DEASETILASI KITOSAN DAN pH PELARUTAN ENZIM TERHADAP KEMAMPUAN IMOBILISASI LIPASE PADA KITOSAN SERBUK - Fandhi Adi Wardoyo (Universitas Muhammadiyah Semarang, 2014)
Immobilization of lipase on chitosan powder was performed. The aim of this research is todetermine the optimum conditions for the immobilization process. Chitosan was prepared fromcrab shell through continous deacetylation, and crosslinked with glutaraldehyde. Immobilizationof lipase on chitosan powder was studied under the optimum conditions e.i. pH optimum oflipase solubility and deacetylation degree of chitosan. Immobilized lipase on chitosan powderwas tested for the activity through the hydrolysis reaction of palm oil. Continous deacetylationproduced chitosans A, B and C with deacetylation degrees of 81.34% , 90.23%, and 92.80%,respectively. The optimum pH for enzyme dissolution was obtained at pH 6. Optimumefficiency of immobilization on chitosans A, B, and C, were 47.67; 40.74 and 38.76%,respectively. Specific activity of free lipase, immobilized lipase on chitosan A, immobilizedlipase on chitosan B and immobilized lipase on chitosan C were 23.94; 0.0435; 0.0178; and0.0175 U/g, respectively.Keywords: lipase, immobilization, chitosan, cross linking